TAFSIR ILMU DALAM AL-QURâAN (Jurnal Ilmu Ushuluddin, 2014)
The Qurâan considers science as the life and light, while ignorance is death and darkness. As it is known, all forms ofcrime due to the lack of life and light, and all the good due to light and life. Because, the light nature open-nature ofthings by explaining levels. Life is the complementary nature of perfection that drives to correct words and deeds. Thispaper describes about the definition of science, the science foundation, the purpose of science, science subject, the objectof science, and science applications in the interpretation of the Koran that uses a combination of methods of maudhuâiand tahlili.